2009
DOI: 10.1007/s10840-009-9443-2
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of arrhythmic storm triggered by monomorphic ectopic beats in patients with coronary artery disease

Abstract: Electrical storm due to focally triggered polymorphic VT/VF may occur either in subacute phase of myocardial infarction or substantially later after index event. Catheter ablation of ectopic beats triggering these arrhythmias can successfully abolish electrical storm and become a life-saving procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 13 publications
3
23
0
7
Order By: Relevance
“…U pacjentów z nawracającym VT lub VF wyzwalanym przez przedwczesne pobudzenia komorowe (PVC) z częściowo uszkodzonych włókien Purkinjego ablacja przezcewnikowa jest bardzo skuteczna i należy ją rozważyć (patrz punkt 6.3.2.) [261][262][263][264][265]. Zaleca się czasową stymulację przezżylną u pacjentów z objawowym blokiem przedsionkowo--komorowym wysokiego stopnia bez stabilnego rytmu zastępczego…”
Section: Stosowanie Leków Antyarytmicznych W Ostrych Zespołach Wieńcounclassified
See 2 more Smart Citations
“…U pacjentów z nawracającym VT lub VF wyzwalanym przez przedwczesne pobudzenia komorowe (PVC) z częściowo uszkodzonych włókien Purkinjego ablacja przezcewnikowa jest bardzo skuteczna i należy ją rozważyć (patrz punkt 6.3.2.) [261][262][263][264][265]. Zaleca się czasową stymulację przezżylną u pacjentów z objawowym blokiem przedsionkowo--komorowym wysokiego stopnia bez stabilnego rytmu zastępczego…”
Section: Stosowanie Leków Antyarytmicznych W Ostrych Zespołach Wieńcounclassified
“…Dokładne przezcewnikowe mapowanie i skuteczna ablacja bodźców wyzwalających VT lub VF bądź też substratu w mięśniu sercowym podtrzymują-cego VT lub VF to złożony i wymagający zabieg. Należy więc rozważyć wczesne kierowanie pacjentów z nawracającymi VF lub VF (burza elektryczna) do wyspecjalizowanych ośrodków ablacyjnych [261][262][263][264][265].…”
Section: Ablacja Przezcewnikowa Nawracającego Utrwalonego Częstoskurcunclassified
See 1 more Smart Citation
“…3, 4 Catheter ablation is effective in the acute suppression of an ES and often represents a life-saving therapy. 5, 6 Substrate mapping generally begins with the identification of the region of ventricular scar, based on the electrogram characteristics (usually voltage) in an electroanatomic map of the ventricle. 2, 7 Human studies have demonstrated that these slow-conduction areas take place in narrow bundles of viable tissue that function as conducting channels bound by scarred tissue.…”
Section: Images In Cardiovascular Medicine Tsai Wc Et Almentioning
confidence: 99%
“…Catheter ablation of culprit premature ventricular complexes (PVCs) responsible for triggering the VF episodes may be required in rare cases of electrical storm that do not respond to conventional measures, and this can be life-saving. (2,3) To date, there have been very few reports on the use of catheter ablation in LQTS patients presenting with VF storm.…”
Section: Introductionmentioning
confidence: 99%